Low Roll‐Off and High Efficiency Orange Organic Light Emitting Diodes with Controlled Co‐Doping of Green and Red Phosphorescent Dopants in an Exciplex Forming Co‐Host. (8th April 2013) - Lee, Sunghun; Kim, Kwon‐Hyeon; Limbach, Daniel; Park, Young‐Seo; Kim, Jang‐Joo
Abstract An exciplex forming co‐host is introduced in order to fabricate orange organic light‐emitting diodes (OLEDs) with high efficiency, low driving voltage and an extremely low efficiency roll‐off, by the co‐doping of green and red emitting phosphorescence dyes in the host. The orange OLEDs achieves a low turn‐on voltage of 2.4 V, which is equivalent to the triplet energy gap of the phosphorescent‐green emitting dopant, and a very high external quantum efficiency (EQE) of 25.0%. Moreover, the OLEDs show low efficiency roll‐off with an EQE of over 21% at 10 000 cdm−2. The device displays a very good orange color (CIE of (0.501, 0.478) at 1000 cdm−2) with very little color shift with increasing luminance. The transient electroluminescence of the OLEDs indicate that both energy transfer and direct charge trapping takes place in the devices.